Взаємини Запорозького і Новослобідського козацтва (1753-1764 рр.). (Zaporizhzhia Historical Review, 2021)
The author explores the relations between Zaporizhzhyan and Novoslobidske Cossackhood. He concludes that these relations were quite ambiguous and were characterized by constant struggle for land estates and also by trade and common conflicts. But while executing military services those conflicts and misunderstanding gave place to mutual aid and cooperation.